Hubungan Pola Makan dan Kepatuhan Mengonsumsi Tablet Tambah Darah dengan Kejadian Anemia Pada Ibu Hamil di UPTD Puskesmas Kauko - Yulita Yulita; Agnes Sry Vera Nababan; Eka Nenni Jairani; Elda Puput Julriang Zebua (Sekolah Tinggi Ilmu Kesehatan Pertamedika, 2023)
Background : In Indonesia, anaemia is a public health issue that requires attention due to its dietary deficiencies. The low compliance of pregnant women with taking blood supplement pills is one of the reasons of anaemia in pregnant women. Pregnant women's noncompliance with taking blood supplement pills may indicate how severe their anaemia will be. In addition, a poor diet that results in insufficient consumption of foods high in iron is one of the reasons of anaemia during pregnancy. Objective : This study is to ascertain the association between the occurrence of anaemia in pregnant women at the UPTD Public Health Centre in Kauko and diet and adherence to using blood supplement tablets. Mehods : This kind of study used a cross-sectional design and quantitative methodology. 74 pregnant women in all were sampled using this approach. Chi-square analysis was done on the data. Result : At Unit of Kauko Community Health Centre, Gunungsitoli District, Gunungsitoli City, the study's findings demonstrated a link between food and the prevalence of anaemia in pregnancy, with the chi-square test yielding a value of (p = 0.00). At Kauko Community Health Centre, Gunungsitoli District, Gunungsitoli City, there was a correlation between the occurrence of anaemia in pregnant women and their adherence to taking blood supplement pills; the chi-square test results yielded a value of (p = 0.00). Conclusion : It was concluded that the incidence of anaemia in pregnant women was correlated with diet and compliance with taking blood supplement pills throughout pregnancy. It was advised that the Kuko Community Health Centre in Gunungsitoli District step up community education, particularly for expectant mothers, on the significance of dietary modifications and the use of blood supplement pills